Analisis Peramalan Permintaan dan Perencanaan Kapasitas Produksi Gas Oksigen Menggunakan Output Standar Produksi - M Iqbal Saputra; Sajiyo Sajiyo (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study analyzes demand forecasting and production capacity planning for oxygen gas at CV Alam Raya Gas using standard output. The data include demand, production realization, process standard time, working days, and capacity cost alternatives. Moving average, exponential smoothing, and linear regression were compared using MAD. Total 2025 demand reached 78,720 cylinders, while production realization was 61,402 cylinders, equal to 78.00% fulfillment. Linear regression produced the lowest MAD of 157.62 and forecasted 39,876 cylinders for January-June 2026. Regular standard output is 31,086 cylinders, leaving a gap of 8,790 cylinders. Four-hour overtime for 78 days is recommended because it covers the gap at a lower cost than adding workers.